ALGEBRAIC THINKING PROFILE OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING PROBLEMS: PERSPECTIVE OF MATH ANXIETY - Novia Sari Susanti; Abadi; Lukito, Agung (IAIN Ambon, 2024)
Algebraic thinking skills need to be developed in students because this ability focuses students on relationships and representations in problem solving. Three Al Falah Surabaya junior high school students were involved in a descriptive qualitative study to explore the algebraic thinking process of junior high school students in the perspective of their mathematics anxiety and problem solving task. Subject was selected by providing anxiety questionnaire content 30 question with 4 choose answer and use questionnaire, math ability test consist of ten question content of algebra for seven and eight grade from national examination forjunior high school which modified. Data were collected through giving problem solving tasks and interviews. The results of this study showed that students with three different anxieties in solving problems presented three indicators of algebraic thinking, including identification, generalization, and application of generalization. The difference is the success rates in using the algebraic thinking indicators. The recommendation of this study is the importance of special attention and treatment from teachers to students with high anxiety who have a tendency to get confused when understanding the problem. Keywords: Algebraic Thinking; Anxiety; Math; Problem-Solving